Scalable production of reduced graphene oxide via biowaste valorisation: an efficient oxygen reduction reaction towards metal-free electrocatalysis. (19th December 2022) - Shah, Asmita; Singh, Harish; Prajongtat, Pongthep; Joshi, Manish Chandra; Hannongbua, Supa; Chattham, Nattaporn; Kim, Young-Ki; Kumar, Sandeep; Singh, Dharmendra Pratap
Abstract : The development of environment-friendly, scalable, and low-cost electrocatalysts for an efficient ORR is important for green energy harvesting. This article deals with the scalable production of N-doped rGO for demonstrating better ORR activity. Abstract : The development of substantial, environment-friendly and low-cost electrocatalysts for an efficient oxygen reduction reaction (ORR) is essentially important for the production and storage of green energy which has sparked the curiosity of researchers for scalable production of metal-free electrocatalysts from biowaste. We report an easy transformation of chestnut-derived biowaste into reduced graphene oxide (rGO) and pyridinic-N-dominated nitrogen-doped rGO (NCS-rGO). The synthesized catalyst exhibits better ORR activity with an onset and half-wave potential of 0.93 V and 0.86 V, respectively, along with a high diffusion-limiting current density of 5.05 mA cm −2 . Under alkaline conditions, we found that NCS-rGO shows an unusually high electrocatalytic activity that is superior to that of the commercial 20% Pt/C catalyst. More notably, the NCS-rGO-based ORR electrocatalyst manifests higher methanol tolerance, without deterioration in catalytic activity even in the presence of significant amount of methanol, outperforming the current state-of-the-art Pt electrocatalyst. Density functional theory (DFT) studies illustrate that pyridinic N is a decisive part of NCS-rGO to achieve the best ORR performance.